The Role of Local Government Area Administrators in The Development of Football in Taraba State Nigeria - Akawu Bitrus Kirim (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: This research investigates the role of Local Government administrators in the development of football in Taraba State, Nigeria. The study aims to explore the contributions of local governments to football development, identify the factors hindering its progress, examine the relationship between local government administration and football development, and evaluate the standards of football facilities in the local government areas of Taraba State. Theoretical framework: The theoretical framework is based on the concept of grassroots sports development, emphasizing the role of local governance in promoting sustainable sports growth. Literature Review: A review of the literature highlights a significant gap in the attention given to football development in rural areas of Nigeria, with existing studies primarily focusing on national-level football advancement. This neglect has adversely affected the growth of the sport in hinterlands such as Taraba State. Methods: The research adopts a descriptive survey design using an ex post facto approach. Data were collected through a structured questionnaire targeting local football players, coaches, teams, and officiating officials in Taraba State. A purposive sampling technique was employed, and a sample size of 300 respondents was selected. Data were analyzed using Mean, Standard Deviation, frequency, percentages, and a one-sample t-test at a 0.05 level of significance. Results: The findings reveal a lack of adequate involvement of local government administrators in football development, poor standards of football facilities, and several factors impeding growth, such as inadequate funding, lack of infrastructure, and insufficient training programs. The results underscore the critical relationship between effective local governance and grassroots sports development. Implications: This study contributes to the existing body of knowledge by highlighting the importance of local government intervention in fostering sports development at the grassroots level. It calls for strategic investments, policy formulation, and active collaboration between stakeholders to revitalize football in Taraba State. Novelty: The novelty of this research lies in its focus on the intersection of local governance and rural football development.